Perubahan Mutu Beras Analog Jagung Selama Penyimpanan dan Penentuan Umur Simpannya dengan Metode Arrhenius - Feri Kusnandar; Mutia Khonza; Slamet Budijanto (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2017)
Corn is a carbohydrate that can be processed into corn-rice analog. The product has acceptable physical and sensory qualities. However, its quality changes during storage and shelf-life has not been reported. The objective of this research was to evaluate quality changes of corn-rice analog during storage and to predict its self-life using accelerated shelf-life testing (ASLT) applying Arrhenius model. Corn-rice analog was stored at 35, 45, and 55oC, and periodically analyzed for 35 days. The analyses included the changes of thio barbituric acid (TBA) number, colour, and sensory quality (rancid odor and color intensity). The TBA number did not inconsistently change during storage. The significant quality changes was due to colour changes (L, a, and b values) of corn-rice analog and rancid odor and color by panelist for corn rice analog before and after cooking. The b value parameter was the most critical quality parameter. Based on its b value, the rice analog had shelf-life of 3 month 17 days at room temperature (25oC).